Comparison of Endobronchial Ultrasound–guided Transbronchial Needle Aspiration With Stylet Retracted Partially Versus Completely for Molecular Testing. Issue 3 (July 2019) - Fernandez-Bussy, Sebastian; Biswas, Abhishek; Labarca, Gonzalo; Jantz, Michael A.; Mehta, Hiren J.
Abstract : Background: Endobronchial ultrasound–guided transbronchial needle aspiration (EBUS-TBNA) is considered to be the initial diagnostic modality for most patients with lung cancer. However, the optimal technique for maximizing yield continues to vary in the real-world setting. Objectives: To evaluate the diagnostic yield of EBUS-TBNA with capillary sampling compared with complete stylet removal for molecular testing. Methods: Retrospective study, data from patients between January to May 2017 with indication of EBUS-TBNA whom ancillary testing, that is, next-generation sequencing, anaplastic lymphoma kinase ( ALK ), and programed death ligand-1 (PD-L1) expression was reviewed. The yield of 2 techniques, stylet retracted halfway (group 1) versus complete retraction (group 2), was compared. Results: A total of 24/27 (88.88%) samples were adequate for next-generation sequencing analysis in group 1 and 21/23 (91.30%) in group 2. For other molecular analyses, 24/27 (88.88%) samples in group 1 and 20/23 (86.95%) samples in group 2 were adequate for ALK analysis. 23/27 (85.18%) samples for group 1 and 20/23 (86.95%) samples for group 2 were adequate for PD-L1 analysis. Positive expression of PD-L1>50% was achieved in 9/23 (39.13%) of group 1 and 5/20 (25%) of group 2. There was no statistical difference in the yield between the 2 groups. Conclusion: EBUS-TBNA using either capillary sampling or complete stylet removal are effective and has a high proportion of satisfactory results for ancillary testing.